THE ROLE OF STREET VENDORS IN THE MORNING MARKETOF TEBAS KUALA VILLAGE IN IMPROVING THE COMMUNITY ECONOMY FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Juniardi, Juniardi; Purnamasari, Wulan; Putra, Purniadi (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The most visible role of the informal sector is its ability to provide job opportunities for people from economically weak groups. With the large number of workers absorbed in the informal sector, especially street vendors around Tebas District, they can indirectly overcome the problem of unemployment in Tebas Kuala Village, especially Tebas District and have an impact on the level of welfare with additional income received by the community around the Morning Market ofTebas Kuala Village and other strategic places as a place of business. Meanwhile, the role played by street vendors is to improve the economy of the people of Tebas District. The focus of this research are: 1) How is the effectiveness of street vendors at the Morning Market in Tebas Kuala Village? 2) What is the Role of Street Vendors in the Morning Market of Tebas Kuala Village from an Islamic Economic Perspective? This study uses a qualitative research with a descriptive approach. Techniques and data collection tools through interviews, observation and documentation. Data analysis using qualitative research includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the effectiveness carried out by street vendors at the Morning Market in Tebas Kuala Village is very effective because the goods sold are very cheap and can meet the needs of the community. As for the role of street vendors, namely 1) Paying retribution to the Tebas Kuala Village Government which will be used as a source of Village Original Income (PADes) but this is not significant, because there are some traders who complain about the management of the Morning Market so they do not pay the retribution. 2) Can help the needs and improve the community's economy but has not been supported by rules that are profitable for the traders of Pasar Pagi Tebas Kuala Village so that our aspirations have not been heard by the Village Government because we have conveyed this through the street vendor community. 3) Can reduce unemployment by opening up employment opportunities with their own business.